The program note as creative knowledge and skills: shaping a collaborative interpretation of newly composed music - Bennett, Dawn; Blom, D. (International Society for Music Education, 2014)
In the classical music concert, a program note provides listeners with information about historical context, personal composer details and the musical thinking behind a work. For repertoire in the Western art music canon, players often know much of this information before they start practicing and then rehearsing the piece; however for newly composed works, the process may be different. This paper reports findings from a practice-led research project involving commissioned works, all of which were received without explanatory program notes. Specifically, the research investigated the preparation of a newly composed work for viola and piano and the role of the program note when it was introduced mid-way through the rehearsal process. In this instance the program note was found to be more of a hindrance than an aid in the building of a collaborative interpretation, yet it remains part of the creative knowledge on which we built a collaborative interpretive platform from which to play the work. The findings emphasise the need for students to utilise their creative knowledge and skills to challenge hierarchies of value as they redefine new repertoire for themselves.